(untitled) (Research, Society and Development, 2020)
Endometritis is the most common clinical form of puerperal infection. It is a common problem in obstetric practice, being the third leading cause of maternal death in Brazil. Accidental home birth, although infrequent, is a risk factor for this affection. This is a retrospective, descriptive and observational study in the form of a case report that seeks to discuss accidental home birth and elucidate the clinical management of puerperal endometritis and retention of placental remains. It is about a patient, who arrives at the hospital service after accidental home birth in good general condition, without complaints and without particularities on physical examination. Days later she developed endometritis and retained placental remains. The necessary measures were taken for adequate therapy, with antimicrobials and curettage. Accidental home birth is considered a mark of social vulnerability, which involves a complex combination of factors, such as sociodemographic conditions, individual values, and the infrastructure of the health service; is responsible for a significant increase in the risk of fetal and neonatal mortality. The unhealthy condition of childbirth predisposes to the development of endometritis and retention of placental remains. The etiology of endometritis is polymicrobial and should be treated with a broad spectrum antimicrobial scheme. Curettage should be used in cases of doubt after detachment, when suspected retention of ovarian remains. Therefore, it is necessary to identify the factors that support the development of puerperal complications in order to have an early intervention and consequent reduction in morbidity and mortality.